Digital Accounting and Taxation Literacy Training for MSME Capacity Building - Maulina Dyah Permatasari; Wisnu Setyawan; Neng Asiah; Lutfia Dhiya Ulhaq (Lentera Pengabdian, 2026)
Micro, Small, and Medium Enterprises play a significant role in supporting regional economic growth; however, they still face challenges in financial management and tax compliance. Limited accounting literacy and low utilization of digital technology often hinder business owners from maintaining proper financial records, preparing financial statements, and fulfilling tax obligations independently. This community service program aimed to strengthen the capacity of business owners through digital-based accounting and taxation literacy. The methods employed included socialization, training, hands-on practice, and mentoring in the use of digital accounting applications and digital tax services. The program was conducted at Universitas Pelita Bangsa and involved nine business owners from Bekasi Regency. The results indicated improvements in participants' understanding and skills in recording financial transactions, preparing simple financial statements, and utilizing digital tax services. Participants were also able to operate digital accounting applications to support more effective and organized business management. The program contributed positively to enhancing managerial capabilities and improving the readiness of business owners to adapt to digital transformation. Therefore, strengthening digital accounting and taxation literacy can serve as an effective strategy to improve professionalism, compliance, and sustainability among micro, small, and medium enterprises.